Reformas estructurales y crecimiento económico en mercados emergentes: un enfoque de complejidad económica - Cossío Montes de Oca, Ernesto Alonso (2020)
Using structural reform indicators for the MSCI Emerging Markets 2018-2019, the effect of economic complexity on economic growth per capita is assessed through a panel data approach using the modern growth accounting methodology. The analysis is made for the period 1995 to 2014, years where good external conditions increased the growth acceleration probability and reduce the deceleration probability. This context was not repeated for the next years, so the search for sources that drives the growth engines is of utmost importance. Economic complexity is the level of know-how a productive structure of a country has, which, according to studies for 128 countries leaded by the economist Ricardo Hausmann and the physicist César Hidalgo, it is found to highly predict current income levels. The results show that economic complexity is not the reform variable that has most encouraged growth; however, it is evident that it is a very relevant variable (top 3) that impacts on the Emerging Markets development, which, if they want to reach the developed zone, they have to work on a strategy to have more diversity and less ubiquity.